Antioxidant, antimicrobial activities and phytochemical analysis of leaves extracts of Dioscorea wallichii Hook. f. - Kokkaiah Irulandi, Sethupandian Geetha, Palanichamy Mehalingam (Journal of Applied Pharmaceutical Science, 2016)
The present study was carried out to evaluate the phytochemical, antioxidant activity and antimicrobial activity of leaf of Dioscorea wallichii. The antimicrobial effect of the studied plant was evaluated on the following bacterial species, Micrococcus mucilaginosus, Escherichia coli, Klebsiella terrigena, Pseudomonas aeruginosa, Bacillus cereus, Staphyllococcus aureus and Candida albicans. The solvents used for the extraction were acetone, ethyl acetate and methanol. The in vitro antimicrobial activity was performed by well diffusion method. The antimicrobial activities of D. wallichii in successive different solvent were tested against Gram positive and Gram negative bacteria and fungus. The extracts showed the presence of flavonoids, coumarins, phenols, tannins, saponins, terpenoids, quinones and catechins. The acetone and methanol extracts of D. wallichii showed the broad spectrum of antimicrobial activity when compared with positive control. The DPPH assay was also conducted for methanolic leaf extract exhibited highest activity which is compare to the activity of the ascorbic acid standard. In conclusion, all organic crude extracts from leaves could be used as potential sources of new antioxidant and antimicrobial agents.
Keywords: Dioscorea wallichii, Phytochemical analysis, Antioxidant, DPPH, Antimicrobial activities.